2022
DOI: 10.1093/annweh/wxac009
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Crosswalk to Translate Italian Occupation Codes to ISCO-68 Codes

Abstract: In occupational epidemiology, job coding is an important—but time-consuming—step in assigning exposure. We implemented a tool (i.e. a crosswalk) to translate occupation codes from the Italian (ISTAT-CIP-91, n = 6319 five-digit job codes) to the International Standard Classification of Occupations (ISCO-68, n = 1881 five-digit job codes). The former is currently used in Italy for various purposes (e.g. in the National Mesothelioma Registry). The latter has been used in several studies on occupational cancers be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Second, our study included MM cases from the whole country and covered a large time window (2000–2018). This was possible thanks to a recently developed crosswalk which allowed translation of thousands of Italian codes of occupations into international (ISCO-68) codes 17. Third, we used three control series for the large majority (95.3% of 2210) randomly sampled from the general population (EAGLE and MISEM studies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, our study included MM cases from the whole country and covered a large time window (2000–2018). This was possible thanks to a recently developed crosswalk which allowed translation of thousands of Italian codes of occupations into international (ISCO-68) codes 17. Third, we used three control series for the large majority (95.3% of 2210) randomly sampled from the general population (EAGLE and MISEM studies).…”
Section: Discussionmentioning
confidence: 99%
“…This was possible thanks to a recently developed crosswalk which allowed translation of thousands of Italian codes of occupations into international (ISCO-68) codes. 17 Third, we used three control series for the large majority (95.3% of 2210) randomly sampled from the general population (EAGLE and MISEM studies). Fourth, analogous to other studies, 19 we could perform analyses in which we excluded subjects employed in non-construction blue-collar occupations for more than 5 years: this approach reduced potential confounding from asbestos exposure in non-construction occupations and yielded relative risk estimates markedly higher than the other approach (in which all subjects were included).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About this last point, coding of job titles from each subject's job history is often challenging and could result in misclassification of exposure [ 40 , 41 , 42 , 43 , 44 , 45 ]. Anyhow, the method applied in this study showed good performances (i.e., sensitivity, specificity, agreement with manual coding) and, overall, it was considered reliable and applicable to efficiently translate Italian job codes (ISTAT-CIP-91) to international job codes (ISCO-68) for the subsequent application of JEMs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coding of industries and jobs was performed by a unique person (CM) using the ATECO-91 Italian ISTAT-CIP-91 coding systems, respectively [ 21 , 22 ]. Consequently, a cross-walk tool [ 23 ] was applied to translate ISTAT-CIP-91 codes into ISCO-1968 codes [ 24 ]. Then, subjects' ISCO-68 codes were linked to SYN-JEM to get yearly intensities of exposure in airborne fibers per mL (f/mL) for each job.…”
Section: Methodsmentioning
confidence: 99%